(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2018)
Low alloy steels are particularly used in manufacturing several parts in the heavyengineering industries, agricultural equipment and dies which may be subject to servicefailure, and thus may need to be repaired by one of the welding processes. The weldabilityof steels is determined by their sensitivity to cracks that can be prevented by the use ofspecial welding procedures which are often expensive and difficult to use. Manual metal arcwelding of low alloy high strength steels was done firstly, using a cheap electrode (OK46.00), followed by the use of an economical technique which depends on coiling copperwires with different diameters around the cheap electrode. The expensive electrode (OK73.68) was also used for comparison. Results showed an increase in the tensile strength (712MPa) and weld joint efficiency (83.8%) when the expensive iron powder low hydrogencovering electrode (OK 73.68) was used. On the other hand, the tensile strength wasdecreased to (206 MPa) and the weld joint efficiency to (24.2%) when the cheap electrode(OK 46.00) was used. Coiling a (0.6 mm) dia. copper wire around the (OK 46.00) electrodeincreased the tensile strength and weld joint efficiency to (510 MPa) and (60%) respectively.